Dietary arsenic exposure in Brazil: The contribution of rice and beans. (February 2017) - Ciminelli, Virginia S.T.; Gasparon, Massimo; Ng, Jack C.; Silva, Gabriela C.; Caldeira, Claudia L.
Abstract: The human health risk associated with arsenic in food in Southeast Brazil was quantified. Based on the most commonly consumed food types in the Brazilian diet, the maximum inorganic As (iAs) daily intake from food (0.255 μg kg −1 body weight per day) is approximately 9% of the Benchmark Dose Lower Limit (BMDL0.5 ) of 3 μg kg −1 body weight per day set by the World Health Organization (WHO) and Food and Agriculture Organization (FAO) Joint Expert Committee in Food Additives (JECFA). When water is included, the contribution of food to the total intake varies from 96.9% to 39.7%. Rice and beans, the main Brazilian staple food, contribute between 67 and 90% of the total As intake from food (46–79% from rice and 11–23% from beans). The substantial contribution of beans to total As food intake is reported for the first time. The broad range of As concentrations in rice and beans highlights the variable and potentially large contribution of both to As food intake in places where diet consists largely of these two food categories. Graphical abstract: Highlights: First comprehensive survey of arsenic intake in the Brazilian diet. Arsenic intake from commonly consumed food types in Brazil was evaluated. Maximum intake from food (0.255 μg of iAs per kg b.w. per day) is 9% of BMDL0.5 Rice and beans contribute between 66% and 90% of the total As intake from food. Substantial contribution of beans to As intake from food is shown.